(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
In this paper, partial ordered relation is researched, finite geometry and its subgeometries are explored. An investigation of topology which exists in near-linear and non-near-linear finite geometry Gd is delved into. The outcome of this work shows an existence of the concept of topology and topological space on non-near-linear finite geometry with variables in Zd. The complexity shown in this work demonstrated the existence of relationship between a geometry as a structure and its subgeometries as its substructures.